Targeting the Degradation of Angiotensin II with Recombinant ACE2: Prevention of Angiotensin II-dependent Hypertension - Wysocki, Jan (2009)
Angiotensin converting enzyme 2 (ACE2) cleaves angiotensin II (Ang II) to form Ang-(1-7). Here we examined whether soluble human recombinant ACE2 (rACE2) can efficiently lower Ang II and increase Ang-(1-7), and whether rACE2 can prevent hypertension caused by Ang II infusion as a result of systemic versus local mechanisms of ACE2 activity amplification. rACE2 was infused via osmotic minipumps for three days in conscious mice or acutely in anesthetized mice. rACE2 caused a dose-dependent increase in serum ACE2 activity but had no effect on kidney or cardiac ACE2 activity. Following Ang II infusion (40pmol/min), rACE2 (1mg/kg/d) resulted in normalization of systolic blood pressure and plasma Ang II. In acute studies, rACE2 (1mg/kg) prevented the rapid hypertensive effect of Ang II (0.2mg/kg), and this was associated with both a decrease in Ang II and an increase in Ang-(1-7) in plasma. Moreover, during infusion of Ang II, the effect of rACE2 on blood pressure was unaffected by a specific Ang-(1-7) receptor blocker, A779 (0.2 mg/kg), and infusing supra-physiologic levels of Ang-(1-7) (0.2 mg/kg) had no effect on blood pressure. We conclude that during Ang II infusion rACE2 effectively degrades Ang II and in the process normalizes blood pressure. The mechanism of rACE2 action results from an increase in systemic, not tissue, ACE2 activity and the lowering of plasma Ang II rather than the attendant increase in Ang-(1-7). Increasing ACE2 activity may provide a new therapeutic target in states of Ang II over-activity by enhancing its degradation, an approach that differs from the current focus on blocking Ang II formation and action.